2019
DOI: 10.17547/kjsr.2019.27.1.17
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison Study of Nurses’Exhaustion and Depression, Anxiety, ADHD, and Impulsivity

Abstract: Objective: This study aimed to evaluate the comparison of exhaustion, ADHD, self-esteem, impulsivity, suicidal tendencies and quality of life as well as depression and anxiety in nurses group and comparison group in Korea. Methods: A set of questionnaires was provided to a total of 97 nurses and 310 other participants as a comparison group. All subjects were evaluated using the Beck'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
0
0
1
Order By: Relevance
“…Exhaustion, a stress-related factor, significantly predicted the level of anxiety. This is supported by studies conducted in Asia that have shown a correlation of psychological distress with exhaustion [43,44]. These findings could be explained by the physical and psychological exhaustion that occur as a result of work commitments and fear of COVID-19 infection.…”
Section: Discussionsupporting
confidence: 54%
“…Exhaustion, a stress-related factor, significantly predicted the level of anxiety. This is supported by studies conducted in Asia that have shown a correlation of psychological distress with exhaustion [43,44]. These findings could be explained by the physical and psychological exhaustion that occur as a result of work commitments and fear of COVID-19 infection.…”
Section: Discussionsupporting
confidence: 54%
“…병원 여성 간호사는 병원 근무의 직업적으로 일반 여성 근로자에 비해 추가적인 일-생활 균형 문제를 겪을 수 있으 나 이를 확인하기 위한 비교 연구는 매우 미진한 상태이다. 지금까지는 간호사와 대조군(예, 여성 임금 근로자) 각각에 대한 연구 결과를 간접적으로 비교했으나 간호사의 근무관 련 이슈를 대조군과 직접 비교 연구도 이루어지고 있다 (Kim YS et al, 2019). 간호사의 일-생활 균형에 대한 국내연구 를 보면, 간호사 대상으로 질적 연구방법으로 일-생활 균형 수준과 영향을 탐색한 연구가 있었으며 (Kim MY, 2012;Kim MY et al, 2015;, 양적 연구로 일-생활 균형의 수준 및 관련 요인을 파악한 연구 (Jung MS et al, 2017), 일-생활 균형의 직무만족, 이직의도 등 일반 적 조직 성과에 미치는 영향을 살펴본 연구 (Han KS et al, 2011;Kim YN et al, 2014;Son DM et al, 2018), 개인 의 삶의 질, 건강에 미치는 영향을 살펴본 연구(Lee YS et al, 2013) 등이 있었다.…”
Section: 서 론unclassified